Cases of Bullying in the School Environment and Its Impact on Children's Future - Eko Setiawan; Sri Wahyuni (Publikasi Inspirasi Indonesia, 2024)
Bullying can occur anywhere, both in urban and rural areas, both public and private schools. Whatever the type, bullying is unjustified. School should be a comfortable place for students to study science, because the impact of bullying causing deep trauma can be felt until adulthood. For this reason, to overcome bullying is not only the task of one person but all parties. This study uses a literature review method obtained online, consisting of various journal articles, research results, and subject books on bullying. Descriptive-analytical data analysis, the researcher organized all the data thoroughly about the bullying phenomenon that had been collected through internet searching. The results of the study show that various types of bullying consist of verbal bullying, cyber bullying, physical bullying, and sexual bullying. The impact of bullying victims, such as experiencing physical and verbal violence, can result in deep trauma to suicide. Special program School Violence Prevention Demonstration Program. Designed school aims to address bullying behavior